2016
DOI: 10.1371/journal.pone.0159789
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bufalin Derivative Exhibited Stronger Apoptosis-Inducing Effect than Bufalin in A549 Lung Cancer Cells and Lower Acute Toxicity in Mice

Abstract: BF211 is a synthetic molecule derived from bufalin (BF). The apoptosis-inducing effect of BF211 was stronger than that of BF while the acute toxicity of BF211 was much lower than that of BF. BF211 exhibited promising concentration-dependent anti-cancer effects in nude mice inoculated with A549 cells in vivo. The growth of A549 tumor xenografts was almost totally blocked by treatment with BF211 at 6 mg/kg. Notably, BF and BF211 exhibited differences in their binding affinity and kinetics to recombinant proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…Recent experimental studies have indicated that Chan Su and its active compound bufalin have significant antitumor activity in various cancers. For example, bufalin can inhibit cancer cell proliferation [ 5 , 6 ], induce cancer cell apoptosis and autophagy [ 7 , 8 ], inhibit cancer metastasis and invasion [ 9 , 10 ], and reverse multidrug resistance [ 11 ]. Studies had found that bufalin inhibits GC proliferation, induces apoptosis, and reverses cisplatin resistance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies have indicated that Chan Su and its active compound bufalin have significant antitumor activity in various cancers. For example, bufalin can inhibit cancer cell proliferation [ 5 , 6 ], induce cancer cell apoptosis and autophagy [ 7 , 8 ], inhibit cancer metastasis and invasion [ 9 , 10 ], and reverse multidrug resistance [ 11 ]. Studies had found that bufalin inhibits GC proliferation, induces apoptosis, and reverses cisplatin resistance [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the concentration inducing cardiotoxicity was estimated as 1 mM which was significantly higher than those exerting anti-tumor effect presented in this manuscript, suggesting clinical usage of bufalin might spare cardiotoxicity. Indeed, there have been several reports showing in vivo findings ( 31 , 32 ). Given the low working concentration of bufalin, as low as nano-molar levels, the achievement of an effective concentration of bufalin should be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its function as an ion pump, NKA is also a multifunctional protein in signal transduction, cell junctions, adhesion and motility ( 33 , 34 ). NKA contains four isoforms of the α-subunit (α1, α2, α3 and α4) and three of the β-subunit (β1, β2 and β3) in vertebrates, and the α-subunit of NKA is the active subunit participated in the binding of cardiac steroids and NKA ( 16 , 35 ). Generally, the α1 subunit is widely expressed in various cell types, and the α2 subunit is mostly expressed in the heart muscle, skeletal muscle and brain.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Bufalin has significant antitumour activity in a wide spectrum of tumour models, such as the inhibition of cell proliferation and angiogenesis, induction of cell differentiation and apoptosis, disruption of the cell cycle, reversal of multidrug resistance and modulation of the immune response ( 13 , 14 ). Numerous studies have indicated that NKA is a main target of Bufalin, and an aberrantly expressed NKA subunit is tightly associated with cell apoptosis and proliferation in several cancers ( 15 , 16 ). However, the effect of Bufalin on cell proliferation and apoptosis of bladder cancer cells has not been thoroughly clarified, and the underlying mediating mechanisms such as antitumour effects remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%